Neoliberalism, Islam and the idea of mankind - Azmat Hayat,; Muhammad Hakimi Muhammad Shafiai,; Muhamad Sabri Haron, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The declaration of neoliberalism as the end of history and final form of mankind ideological evolution is in sharp contrast to the claim of Muslims who believe that Islam already provided an everlasting ideology for the welfare of humanity. This study, therefore, intends to thoroughly compare the claims of these contrasting ideologies by taking the gnosis of mankind. Regarding the methodology of article, clear and logical arguments are used for clarifying the ambiguity surrounding the topic under consideration. In neoliberalism, there is complete silence on the issue of the human incorporeal soul while in case of Islam, Muslims philosophers explained it in a sensible and easy to understand manner. Neoliberalism which motivates human being for selfishness and maximization of profit are associated with violence and corruption across the planet. As an ideological innovation, it is responsible for making human being as selfish, lonely, closed, insatiable and unhappy. Regarding the gnosis of mankind, recent scientific discovery strengthens and support the claim of Muslim philosophers.